2014
DOI: 10.1016/j.joca.2014.02.276
|View full text |Cite
|
Sign up to set email alerts
|

Possible chondroprotective effect of canakinumab: An in vitro study on human osteoarthritic chondrocytes

Abstract: chondro-induction). Chondro-induction was lower (1.3AE0.4) and less reproducible when coculture was performed with M14 and did not occur with skin fibroblasts. GAG contents of constructs generated by solely macrophages were undetectable. Histological analyses of constructs confirmed the biochemical results. In the coculture there was no modulation of the chondrogenic genes. As compared to monocultures, in co-culture MSC and M24 numbers decreased less markedly (at day 7, MSC were 84% and 42% of the initial numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Mitochondrial dysfunction occurs during OA progression (8, 9) and manifests as decreased ATP synthesis, decreased membrane potential, and increased oxidative stress, resulting in cartilage destruction (39). Mitochondrial dysfunction induces IL-1b release and leads to in ammation in chondrocytes by decreasing respiratory chain complex activity (6, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction occurs during OA progression (8, 9) and manifests as decreased ATP synthesis, decreased membrane potential, and increased oxidative stress, resulting in cartilage destruction (39). Mitochondrial dysfunction induces IL-1b release and leads to in ammation in chondrocytes by decreasing respiratory chain complex activity (6, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Canakinumab, a human mAb that neutralizes IL-1β, can significantly downregulate the expression of MMP-1, MMP-3, and MMP-13 in human OA chondrocytes induced by TNF-α and IL-1β by blocking IL-1β interaction with its receptor, exerting potential chondroprotective effects ( Cheleschi et al, 2015 ). In an exploratory clinical trial, canakinumab reduced the overall hip or knee arthroplasty rate in patients with a history of OA at baseline ( Schieker et al, 2020 ).…”
Section: Anti-cellular Senescence Strategiesmentioning
confidence: 99%
“…However, there have been further developments in the use of IL-1 in treating OA, involving canakinumab, a monoclonal antibody targeting IL-1β. Previous in vitro studies of canakinumab on human chondrocytes demonstrated increased proteoglycan and reduced nitric oxide synthesis which may reduce cartilage breakdown [ 98 ]. Canakinumab was recently studied in the CANTOS trial: a very large randomised, placebo-controlled trial investigating the cardiovascular effect of subcutaneous canakinumab [ 99 ].…”
Section: Immunomodulatorsmentioning
confidence: 99%